Evaluation of cord blood alkaline phosphatase levels as an indicator of neonatal jaundice - Doha Mohammed El-Amin; Yasser Abd El-Rheman Ahmed; ALaa Mohammed Hashim; Ahmed Hagag Asmail (Wolters Kluwer Medknow Publications, 2020)
Introduction Neonatal jaundice remains an important neonatal issue, and the condition is mostly benign. Jaundice is a complex disease of high bilirubin levels in the body and yellowing of the skin and mucous membranes. Hyperbilirubinemia is associated with encephalopathy and kernicterus, resulting in permanent disability. Because babies are discharged early, detection and diagnosis of hyperbilirubinemia are delayed in some cases. Therefore, early diagnosis of jaundice and timely actions are necessary. Several methods have been used to determine the risk of neonatal hyperbilirubinemia. Alkaline phosphatase (ALP) is an intracellular enzyme found abundantly in red blood cells. It is a hydrolase enzyme and responsible for removing phosphate from many types of molecules. Our aim in this study was to investigate whether cord blood ALP level during the first 6 h of live of newborn could be used for the early diagnosis and prediction of hyperbilirubinemia in newborns. Patients and methods This was a prospective study carried out during the period from June 2018 to December 2018 at El-Mania General Hospital. This study included a total of 60 neonates: 30 full-term infants and 30 preterm infants. A total of 60 babies were evaluated, starting from the sixth hour after birth, and cord blood ALP levels were analyzed. We performed an assessment of the complete medical history (maternal history and neonatal history). Third day of live measured transcutaneous bilirubin of neonate, and seventh day we measured serum bilirubin (total and direct). Results The present study showed that infants with high cord blood ALP levels are at risk of developing significant indirect neonatal hyperbilirubinemia that requires interventions with an accuracy of 82.2%, a sensitivity of 72%, a specificity of 85.71%, a positive predictive value of 83.43%, and a negative predictive value of 75.37%. Conclusion The cord blood ALP level can be used as a predictor of severe neonatal jaundice.